Evaluating the Integration of Environmental Impact Assessment and Construction Social Costs - Zanyar Omar Abdullah; Tahir Çelik; Tolga Çelik (Journal of Studies in Civil Engineering)
Construction activities often give rise to significant social challenges, including noise, air pollution, and disruptions to daily routines, particularly in residential areas. These challenges are more severe in developing nations like Iraq, where weak building regulations fail to enforce measures that could reduce these effects, leading to elevated social costs. The inconsistent enforcement of regulations across regions further worsens the problem. This study examines the integration of environmental impact assessment with social construction costs. To achieve this, a combination of qualitative and quantitative methods was employed. The questionnaire focused on identifying the negative impacts of construction on the public and assessing the extent of these social costs across fifteen selected projects. Additionally, twenty-one voluntary participants were interviewed using semi-structured interviews. The framework developed in this research provides a valuable approach to considering social costs within environmental impact assessments, making it a crucial aspect of impact studies. Results from the questionnaire showed that, among 195 respondents, over 55% faced high noise and dust levels, 68% experienced road closures, 56% reported pedestrian disruptions, which were accompanied by a corresponding rise in public complaints, and 25% of projects were temporarily halted. However, construction sites generate numerous negative effects, with noise, dust, air pollution, and disruptions to pedestrian activities being the most significant concerns for nearby communities. Over the past five years, complaints about road closures, pollution, and damage to surrounding areas have notably increased. The framework introduced in this study bridges biophysical and social aspects of construction impacts, promoting sustainable planning and improving environmental assessment processes.